2007
DOI: 10.1016/j.crvi.2007.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Bill and hyoid apparatus of pigeons (Columbidae) and sandgrouse (Pteroclididae): A common adaptation to vegetarian feeding?

Abstract: For the present study, 15 species of pigeons representing the 5 sub-families usually recognized, and 3 species of sandgrouse were examined. The skeleton and musculature of the bill and hyoid apparatus are described. Morpho-functional analyses show that from a key adaptation to the removal and deglutition (without processing) of attached plant items, pigeons would have followed two pathways, one based on the joint muscular control of the movement of the jaws (Columbinae, Treroninae, Gourinae), the other on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Muscle Branchiomandibularis is well developed and it is responsible with the other extrinsic lingual muscles for protraction and retraction of the tongue during feeding as well as adduction of the paired hyoid horn. This is in accordance with Korzun et al (2008) in pigeons and sand grouse. Igwebuike and Anagor (2013) demonstrated that the oropharynx and tongue of the Muscovy duck exhibit certain anatomical features and the morphological modifications of this region of the digestive tract may be adaptations to the bird's habitat and mode of feeding.…”
Section: Discussionsupporting
confidence: 74%
“…Muscle Branchiomandibularis is well developed and it is responsible with the other extrinsic lingual muscles for protraction and retraction of the tongue during feeding as well as adduction of the paired hyoid horn. This is in accordance with Korzun et al (2008) in pigeons and sand grouse. Igwebuike and Anagor (2013) demonstrated that the oropharynx and tongue of the Muscovy duck exhibit certain anatomical features and the morphological modifications of this region of the digestive tract may be adaptations to the bird's habitat and mode of feeding.…”
Section: Discussionsupporting
confidence: 74%
“…However, pigeons reveal a considerable and as yet unexplained diversity in their temporal region (Martin, ) and in some species (e.g., Didunculus strigirostris, Treron calva ) the PP remains relatively strong and in a dorsal position, suggesting a corresponding diversity in the structure of m. adductor mandibulae externus. In contrast to the majority of pigeons, the pars media of this muscle extends relatively far rostrally in Didunculus, as well as Otidiphaps (Korzun et al., ; Geophaps was not studied), which explains at least the strength of PZ. In addition, in Didunculus the lateral part (venter externus) of m. pterygoideus inserts on the OZJ instead of the mandible as in other pigeons and most other birds (Burton, ).…”
Section: Discussionmentioning
confidence: 96%
“…In the majority of pigeons, the pars media of m. adductor mandibulae externus is constrained to a caudal position by hypertrophy of the m. pseudotemporalis profundus (Korzun, Erard, Gasc, & Dzerzhinskiy, ), which explains the weakness and reduction in both PP and PZ and the prevailing ventral position of PP. However, pigeons reveal a considerable and as yet unexplained diversity in their temporal region (Martin, ) and in some species (e.g., Didunculus strigirostris, Treron calva ) the PP remains relatively strong and in a dorsal position, suggesting a corresponding diversity in the structure of m. adductor mandibulae externus.…”
Section: Discussionmentioning
confidence: 99%
“…, 2001, 2003, 2008; Perrins, 2004; Herrel et al, 2005; Estrella and Masero, 2007; Baussart and Bels, 2007; Baussart et al, 2009). The majority of studies have focussed on the mechanics of the bill, which has been thoroughly analyzed because cranial kinesis is a key feature of the avian feeding mechanism (McDowell, '48; Bock, '64; Zusi, '84; Korzoun et al, 2000, 2001, 2003, 2008; Bout and Zweers, 2001; Gussekloo et al . , 2001; Gussekloo and Bout, 2002, 2005a, b) and the relationship between bite beak morphology and bite force (Herrel et al .…”
mentioning
confidence: 99%
“…In birds, the neck, beak, and hyolingual structures also show an exceptional degree of variation correlated with diversity of the exploited food (Zusi, '62; Bock, '64; Zusi and Storer, '69; Burton, '74; McLelland, '79; Zweers, '82a, b; Zusi, '84; Zusi and Bentz, '84; Fritsch and Schuchmann, '86; Zweers et al, '94; Homberger, '99; Rubega, 2000; Tomlinson, 2000, Korzoun et al . , 2001, 2003, 2008; Perrins, 2004; Herrel et al, 2005; Estrella and Masero, 2007; Baussart and Bels, 2007; Baussart et al, 2009). The majority of studies have focussed on the mechanics of the bill, which has been thoroughly analyzed because cranial kinesis is a key feature of the avian feeding mechanism (McDowell, '48; Bock, '64; Zusi, '84; Korzoun et al, 2000, 2001, 2003, 2008; Bout and Zweers, 2001; Gussekloo et al .…”
mentioning
confidence: 99%